MENINGKATKAN KETERAMPILAN MAHASISWA DALAM MEMAHAMI TINGKAH LAKU BERBASIS TEORI KEPRIBADIAN MELALUI IMPEMENTASI œPEMBELAJARAN PENGALAMAN LANGSUNG DAN œPEMBERIAN UMPAN BALIK YANG BERDAMPAK PADA SELF EFFICACY ENCREASING THE STUDENT™S SKILL IN UNDERSTAND - S.Psi,MS, Prof. Asih Menanti (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2015)
ABSTRACT This study done was caused by the existing needs to be competent guidance and counseling student in understanding the student™s behavior. The objective of this study were to encrease the guidance and counseling student™s skill and knowledge in arranging and implementing instrument as well as interpreting the student™s behavior based on the personality theory. This study is classroom action research done in two cycles, each cycles consist of three time lecturing sessions. The result of this study show that the subject matter learning about understanding behavior in the subject of personality theory which implement œthe direct exspriences and œthe feedback presentation pronote the student™s competence and mastery in understanding, the student™s behavior, and influence on their self efficacy promotion. It is concluded that learning that implement, œthe direct experience and œthe feedback presentation were alternatively applicable by lectures in encreasing the student™s competence to understand behavior and to encrease self efficayy. Keywords : The understanding  behavior, the direct exsprience and feedback.